Pengaruh Model Kooperatif Tipe Talking Stick terhadap Hasil Belajar Tematik Terpadu Kelas V SD - Ulfa Farika; Tin Indrawati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
The purpose of this study is to find out the effect of Cooperative Learning Model through Talking Stick on the integrated theatic learning outcomes of the fifth year elementary school students in Elementary School Cluster 4 in Padang Timur Sub-District, Padang. This study used a quasi-experimental design in the form of nonequivalent control group design. The sampling technique used was cluster random sampling. The sample of this study was the fifth year elemtary schol students in Elementary School Cluster 4 in Padang Timur Sub-District, Padang.18 students at Class VB of SDN 35 Parak Karakah were chosen as the experimental class, and 22 students of SDN 17Parak Karakah were chosen as the control class. The results of this study show that the average pretest score of the experimental class is 54,07, and the average pretest score of the control class is 54. Meanwhile, the average scores of the both the experimental class and control class are 84,07 and 64,94, respectively.furthermore, the results of the analysis of the hypothesis testing at a significance level of 5% are tcount>ttable (6.13 > 2,024), soit can be concluded that using Cooperative Learning Model through Talking Stick elementaryschool students in Elementary School Cluster 4 in Padang Timur Sub-District, Padang.